Transport into the polar stratosphere from the Asian monsoon region - X. Yan; P. Konopka; F. Ploeger; F. Ploeger; A. Podglajen (Atmospheric Chemistry and Physics)
The Southeast Asian boundary layer has witnessed alarming pollution levels in recent years, which even affects the trace gas composition in the Southern Hemisphere by inter-hemispheric transport. We use SF6 observations and the Lagrangian chemistry transport model Chemical Lagrangian Model of the Stratosphere (CLaMS), driven by the ERA5 reanalysis data for the period 2010–2014, to assess the impact of the Asian monsoon (AM) region (15–45° N, 30–120° E) as a significant source of pollutants for the stratosphere, in particular in polar regions. We examine the contribution of transport from the AM region to the Northern Hemisphere polar region (NP) (60–90° N) and to the Southern Hemisphere polar region (SP) (60–90° S). Despite the smaller geographical size of the AM region when compared to the Southern Hemisphere subtropics (15–45° S) and the tropics (15° S–15° N), our findings reveal that the air mass fractions from the AM to the polar regions are approximately 1.5 times larger than the corresponding contributions from the Southern Hemisphere subtropics and only about 2 times smaller than those from the tropics. The transport of air masses from the AM boundary layer to the stratospheric polar vortex primarily occurs above an altitude of about 450 K and over timescales exceeding 2 years. In contrast, transport timescales to the polar regions situated below the vortex are shorter, typically less than about 2 years. Furthermore, the transport contribution from the AM region to the polar regions exhibits distinctive inter-annual variability, significantly influencing the distributions of pollutants. Our analysis of detrended SF6 from an Atmospheric Chemistry Experiment Fourier transform spectrometer (ACE-FTS) over the polar regions reveals a strong correlation with the fraction of relatively young air (less than 2 years old) originating from the AM, Southern Hemisphere subtropics, and the tropics. Importantly, our reconstructed SF6 data indicate that approximately 20 % of SF6 in both the northern and southern polar stratosphere originates from the AM boundary layer. The largest fraction of SF6 in the polar stratosphere still originates from the tropical boundary layer, contributing about 50 % of SF6.